Business law - Mallor, Jane P (McGraw-Hill/Irwin, 2010)
Includes bibliographical references and index; 11 parts: Foundations of American Law; Crimes and Torts; contracts; sales; property; credit; commercial paper; agency law; partnerships; corporations; regulation of business